The man of gold Superman. Man of Steel - Superman, Weissburg Paul; Levins, Tim (North Mankato, MN Stone Arch, 2012)
A new superhero in Metropolis, Booster Gold, seems more interested in glory and popularity, so a suspicious Superman decides to find out just who this person is
Comic strips
a gift from book of africa
1 2 13
Keywords: Superman -- (Fictitious character) -- Juvenile fiction; Supervillains -- Fiction